"Y" incision and rectangular patch enlargement of aortic annulus and valve reconstruction with autologous pericardium in congenital aortic stenosis. Issue 12 (8th November 2022) - Jaswal, Vivek; Bansal, Vidur; Chakraborty, Nirupam Sekhar; Rohit, Manoj Kumar; Thingnam, Shyam Kumar Singh
Abstract: Surgical aortic valve replacement in children who have undergone prior balloon or surgical valvuloplasty or both is a formidable challenge. The aortic annulus is small, there is no ideal prosthesis and lifelong anticoagulation is highly undesirable. A "Y" incision and rectangular patch enlargement of the aortic annulus introduced by Dr. Bo Yang in 2020 combined with aortic valve reconstruction introduced by Dr. Shigeyuki Ozaki in 2011, is feasible, as described in this case.